A EXCELÊNCIA HISTORIOGRÁFICA NOS PRIMÓRDIOS DA ACADEMIA REAL DAS CIÊNCIAS DE LISBOA (1779-1820) - Dias, Eurico Gomes (2017)
At the time of creation of the Royal Academy of Sciences [1779] will be initiated multiple scientific  efforts  to  renew  the  portuguese  historiography.  One  of  the  best  examples,  among  other academic  and  university  initiatives,  was  the  compilation  of Memórias  de  Litteratura  Portugueza[vols.  I-VIII,  1792-1814],  which  contain  the  best  historiographical  works  published  between  the late  eighteenth  century  and  early  nineteenth  century,  which  pointed  the  way  for  the  triumph  of scientific historiography activity.